FOOD AND FEEDING HABITS OF PENNAHIA MACROPHTHALMUS BLEEKER AT VISAKHAPATNAM - Rao, T Appa (Indian Journal of Fisheries, 2011)
The food and feeding habits of Pennahia macrophthalmus Bleeker, asciaenid occurring in the trawl catches at Visakhapatnam, wis studied during theperiod March 1%8-Decem'b2r 1973. P. macrophthalmus is a macrbphagous carnivorefeeding on teleosts and prawns. Among the teleosts, Bregmaceros macclellandiand Anchoviella sp. are predominant. Prawns namely Penaeus s:pL, Metapenaeussp., Acetes sp. are found to be major components among the crustaceans. Study offood in relation to different size groups showed P. macrophthalmus became moreicthyophagous w^th age. Low feeding between February-April, moderate feedingbetween May-July and high feeding during the rest of the months seemed to prevail